(untitled) (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.5956.1-4 Apresenta a 2a. edição da Revista Gestão & Conexões (Management and Connections Journal), v2, n2, jul./dez. 2013.